Antibody to a recombinant merozoite protein epitope identifies horses infected with Babesia equi. - Knowles, D P (1992)
Horses infected with Babesia equi were previously identified by the presence of antibodies reactive with a merozoite surface protein epitope (D. P. Knowles, Jr., L. E. Perryman, L. S. Kappmeyer, and S. G. Hennager. J. Clin. Microbiol. 29:2056-2058, 1991). The antibodies were detected in a competitive inhibition enzyme-linked immunosorbent assay (CI ELISA) by using monoclonal antibody 36/133.97, which defines a protein epitope on the merozoite surface. The gene encoding this B. equi merozoite epitope was cloned and expressed in Escherichia coli. The recombinant merozoite protein, designated equi merozoite antigen 1 (EMA-1), was evaluated in the CI ELISA. Recombinant EMA-1 bound antibody from the sera of B. equi-infected horses from 18 countries. The antibody response to EMA-1 was then measured in horses experimentally infected with B. equi via transmission by the tick vector Boophilus microplus or by intravenous inoculation. Anti-EMA-1 antibody was detected 7 weeks post-tick exposure and remained, without reexposure to B. equi, for the 33 weeks of the evaluation period. The data indicate that recombinant EMA-1 can be used in the CI ELISA to detect horses infected with B. equi.